Accurate diagnosis and sub categorization of benign adenomyoepithelioma of the breast-tubular type: A challenge on core needle biopsy - Prita Pradhan; Saranya Mohan; Arun K Kumar; Debasis Gochhait; Pampa Chi Toi; Jagdish Sadasivan (Wolters Kluwer Medknow Publications, 2019)
Adenomyoepithelioma (AME) is a biphasic myoepithelial tumor with poorly understood histogenesis. Most of these cases have a benign course. They can cause major diagnostic dilemmas, particularly on core needle biopsy. Here we report of a case of a benign adenomyoepithelioma in a fourty-four year old female who presented with hard breast lump, which highlights the diagnostic difficulties encountered on conventional histopathology and the importance of immunohistochemistry in differentiating them from their mimics.